Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
Judges Stephen Henry and Frank Creede Jr. and Larry Viau Jr. listening to William A. Smith, Edward Marouk 5080 E. Kings Canyon Road, Fresno